Perception of MSMEs in the Use of Ecommerce to Improve the Accuracy of Sales and Inventory Information Systems - Putra, Yananto Mihadi (Jurnal Profita: Komunikasi Ilmiah Akuntansi dan Perpajakan, 2023)
The development of information technology is very rapid accompanied by the advancement of technology-based information systems. Technology makes a significant contribution by providing various conveniences for companies or organizations. One of the fields that is highly affected is Micro, Small, and Medium Enterprises (MSMEs). Although e-commerce has been widely used by MSMEs to increase sales and profitability, there are still challenges in measuring the effectiveness of accounting information systems implemented through e-commerce. This study aims to find out how effective the accounting information system is for MSME actors who use e-commerce. The main focus is to measure the impact of the use of e-commerce on the accuracy of sales information (IP) and profitability (PT) on MSMEs. The method used in this study is a descriptive quantitative approach. The independent variables studied were the accuracy of sales information (IP) and profitability (PT), while the dependent variable was the use of e-commerce (PE). Data was collected through a survey method from MSMEs using e-commerce in Jakarta, with a random sampling technique based on area (Cluster Random Sampling). The research instrument in the form of a questionnaire with a Likert scale was used to measure user perception related to the variables studied. The results of the study show that the use of e-commerce significantly improves the accuracy of sales and inventory information systems in MSMEs. Statistical analysis shows that the independent variables of sales information accuracy (IP) and profitability (PT) have a significant effect on the dependent variables of e-commerce use (PE). The description of the characteristics of the respondents showed that the majority of respondents were MSME owners or managers with more than five years of experience in using e-commerce, and had an education level at the S1 level. The use of e-commerce has a positive and significant effect on the accuracy of the sales and inventory information system for MSMEs in Jakarta. E-commerce has proven to be an effective tool to increase the efficiency and profitability of MSMEs.